Efecto antibacterial in vitro del extracto etanolico de Hibiscus sabdariffa L. sobre cepas de Streptococcus mutans - Padilla, Luis (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
Dental caries is one of the most frequent diseases worldwide and due to its prevalence, phytotherapy began to be used as an alternative treatment. Hibiscus sabdariffa L. has a wide variety of therapeutic properties, of which its antibacterial activity stands out in this study. Objective: The objective of this research was to determine the in vitro antibacterial effect of the ethanolic extract of Hibiscus sabdariffa L. on strains of Streptococcus mutans at 24 and 48 hours. Materials and methods: The research was applied to experimental design and prospective measurement. The sample was obtained from patients who signed the informed consent in order to obtain the Streptococcus mutans strains. They were cultivated in 16 Petri dishes and 7 discs of filter paper No. 4 were distributed in each plate, the technique was Kirby Bauer disc diffusion with wells, with a total of 112 discs and wells; the Petri dishes were divided into 4 groups according to the concentrations of the ethanolic extract of Hibiscus sabdariffa L. that was obtained by maceration with 96% alcohol to obtain a sample of 100% ethanolic extract of Hibiscus sabdariffa L. and to obtain the concentrations of 25%, 50% and 75% alcohol was used to make the dilutions. Chlorhexidine 0.12% was considered as positive control and distilled water as negative control. Results: It was shown that Hibiscus sabdariffa L. has an inhibitory effect. The best effect was recorded at 48 hours at 100% concentration. Obtaining an inhibition halo of 14.23mm. Conclusion: The ethanolic extract of Hibiscus sabdariffa L. does have an in vitro antibacterial effect on Streptococcus mutans strains.